Is iron treatment beneficial in, iron-deficient but non-anaemic (IDNA) endurance athletes? A systematic review and meta-analysis. Issue 21 (31st October 2014) - Burden, Richard J; Morton, Katie; Richards, Toby; Whyte, Gregory P; Pedlar, Charles R
Abstract : Purpose: The aim of this study was to determine whether iron treatments improve the iron status and aerobic capacity of iron deficient non-anaemic endurance athletes. Method: A meta-analysis of studies that investigated the effects of iron treatment on serum ferritin (sFer), serum iron (sFe), transferrin saturation (Tsat), haemoglobin concentration ([Hb]) and ( ). Seventeen eligible studies were identified from online databases. Results: Analysis of pooled data indicated that iron treatments had a large effect on improving sFer (Hedges' g=1.088, 95% CI 0.914 to 1.263, p<0.001), sFe (Hedges' g=1.004, 95% CI 0.828 to 1.181, p<0.001) and Tsat (Hedges g=0.741, 95% CI 0.564 to 0.919, p<0.001) and a moderate effect on improving [Hb] (Hedges' g=0.695, 95% CI 0.533 to 0.836, p<0.001) and (Hedges' g=0.610, 95% CI 0.399 to 0.821, p <0.001). Regression analysis revealed a significant interaction between the effect of iron treatment on sFer and treatment duration, suggesting treatments that lasted beyond 80 days appear to have the least effect on sFer. Conclusions: These results indicate iron treatments improve the iron status and aerobic capacity of iron deficient non-anaemic endurance athletes.